Decision Making for Principal-Agent Contracts in Intelligent Customization for New Energy Equipment. (16th December 2019) - Meng, Fansheng; Song, Peng; Zhao, Gang
Abstract : Intelligent manufacturing is a sustainable impetus to development of customization for new energy equipment. Reasonable principal-agent contract decision making can play a positive role in improving utility for customers and securing their long-term involvement. This paper establishes a multistage principal-agent model of intelligent customization for new energy equipment. The principal-agent and intelligent customization decisions, yielding risk avoidance and a better cost-benefit ratio, emerged from solving the model. A decision modification mechanism, used to improve intelligent customization output and consolidate customer trust, was proposed for agents. Research shows that overavoidance of customization risk by new energy equipment manufacturers reduces the efficiency of intelligent customization and aggravates the cost-benefit dilemma. Viewing intelligent customization as a long-term cooperative process, manufacturers can achieve a larger increase in equipment customization output at a smaller cost and enhance customer trust by adopting such a decision modification mechanism. The effect of this mechanism is obvious when the risk intensity is low. However, under the assumption of a multistage model, improvement of customer utility is mainly influenced by risk controllability. This paper provides solutions to the risk avoidance and cost-benefit dilemma problems of intelligent customization. The static principal-agent model was improved to a multistage model by setting the timeline. Long-term effectiveness of the decision modification mechanism was verified using this multistage model.